A new and sustainable service to slow fashion brands - Bernardes, João Pedro (2018)
This paper explores the creation of an innovative clothing rental service, that is inspired by the ‘slow fashion movement’, and that focuses on the question: “are people willing to use second-hand clothing and/or leased when travelling?”. This is a rental service for the day-to-day and also business clothing. The creation and development of this service was possible through the use of a design thinking methodology: the 9 steps framework by Kees Dorst. Regarding its validation, it was achieved with a questionnaire with 430 responses. The paper culminates with the positive response to the problem.